The Epipeptide YydF Intrinsically Triggers the Cell Envelope Stress Response of Bacillus subtilis and Causes Severe Membrane Perturbations - Popp, Philipp F.; Benjdia, Alhosna; Strahl, Henrik; Berteau, Olivier; Mascher, Thorsten (Frontiers in Microbiology, 2020)
The Gram-positive model organism and soil bacterium Bacillus subtilis naturally produces a variety of antimicrobial peptides (AMPs), including the ribosomally synthesized and posttranslationally modified AMP YydF, which is encoded in the yydFGHIJ locus. The yydF gene encodes the pre-pro-peptide, which is, in a unique manner, initially modified at two amino acid positions by the radical SAM epimerase YydG. Subsequently, the membrane-anchored putative protease YydH is thought to cleave and release the mature AMP, YydF, to the environment. The AMP YydF, with two discreet epimerizations among 17 residues as sole post-translational modification, defines a novel class of ribosomally synthesized and post-translationally modified peptides (RiPPs) called epipeptides, for which the mode-of-action (MOA) is unknown. The predicted ABC transporter encoded by yydIJ was previously postulated as an autoimmunity determinant of B. subtilis against its own AMP. Here, we demonstrate that extrinsically added YydF* kills B. subtiliscells by dissipating membrane potential via membrane permeabilization. This severe membrane perturbation is accompanied by a rapid reduction of membrane fluidity, substantiated by lipid domain formation. The epipeptide triggers a narrow and highly specific cellular response. The strong induction of liaIH expression, a marker for cell envelope stress in B. subtilis, further supports the MOA described above. A subsequent mutational study demonstrates that LiaIH – and not YydIJ – represents the most efficient resistance determinant against YydF* action. Unexpectedly, none of the observed cellular effects upon YydF* treatment alone are able to trigger liaIH expression, indicating that only the unique combination of membrane permeabilization and membrane rigidification caused by the epipetide, leads to the observed cell envelope stress response.